Effects of SLCO1B1 and GATM gene variants on rosuvastatin-induced myopathy are unrelated to high plasma exposure of rosuvastatin and its metabolites - Bai Xue; Zhang Bin; Wang Ping; Wang Guan-lei; Li Jia-li; Wen Ding-sheng; Long Xing-zhen; Sun Hong-shuo; Liu Yi-bin; Huang Min; Zhong Shi-long (Acta Pharmacologica Sinica, 2019)
Myotoxicity is a signiﬁcant factor contributing to the poor adherence and reduced effectiveness in the treatment of statins. Genetic variations and high drug plasma exposure are considered as critique causes for statin-induced myopathy (SIM). This study aims to explore the sequential inﬂuences of rosuvastatin (RST) pharmacokinetic and myopathy-related single-nucleotide polymorphisms (SNPs) on the plasma exposure to RST and its metabolites: rosuvastatin lactone (RSTL) and N-desmethyl rosuvastatin (DM-RST), and further on RST-induced myopathy. A total of 758 Chinese patients with coronary artery disease were enrolled and followed up SIM incidents for 2 years. The plasma concentrations of RST and its metabolites were determined through a validated ultra-performance liquid chromatography mass spectrometry method. Nine SNPs in six genes were genotyped by using the Sequenom MassArray iPlex platform. Results revealed that ABCG2 rs2231142 variations were highly associated with the plasma concentrations of RST, RSTL, and DM-RST (Padj < 0.01, FDR < 0.05). CYP2C9 rs1057910 signiﬁcantly affected the DM-RST concentration (Padj < 0.01, FDR < 0.05). SLCO1B1 rs4149056 variant allele was signiﬁcantly associated with high SIM risk (OR: 1.741, 95% CI: 1.180–2.568, P = 0.0052, FDR = 0.0468). Glycine amidinotransferase (GATM) rs9806699 was marginally associated with SIM incidents (OR: 0.617, 95% CI: 0.406–0.939, P = 0.0240, FDR = 0.0960). The plasma concentrations of RST and its metabolites were not signiﬁcantly different between the SIM (n = 51) and control groups (n = 707) (all P > 0.05). In conclusion, SLCO1B1 and GATM genetic variants are potential biomarkers for predicting RST-induced myopathy, and their effects on SIM are unrelated to the high plasma exposure of RST and its metabolites.